Rejuvenating Islamic thought and civilization - Abd. Rahman, Akmal Khuzairy (IIUM Press, International Islamic University Malaysia, 2018)
This book is the refined version which contains selected research papers which submitted to the 3rd International Social Science Conference - Islamic Thought & Understansing (ISSCITU 2018), organised by University Teknologi MARA (UiTM) Perlis and The Office of The Sultan Haji Ahmad Shah Mosque, International Islamic University Malaysia. It addresses the ideas of promoting peaceful Islam and strengthening the spiritual dimensions of faith and practice. Hence, the book focuses on the role of Islamic institutions in rejuvenating for Muslims discussions on contemporary issues, challenges and solutions.